Sport-related aspects of preparation for participation in e-sports tournaments based on the game Magic: the Gathering = Sportowy wymiar przygotowań do współzawodnictwa w e-sporcie: na przykładzie gry Magic: the Gathering - Jasny, Michał; Sodomirski, Tomasz (Zielona Góra: Lubuskie Towarzystwo Naukowe)
Video game tournaments are an increasingly popular part of postmodern sport. While electronic sport, or e-sports, has a common functionality with traditional sport, it has not yet been recognised as a sports discipline due to the debatable nature of competitive gaming as an activity. The aim of this study was to investigate the attitudes of experienced competitive players of Magic: The Gathering and their training regimes for esports tournaments in order to determine whether such training is comparable to that in traditional sport.
Keywords: sport; e-sports; training; Magic: The Gathering; e-sport; trening